Diabetic Ketoacidosis Post Bariatric Surgery - Rizo, Ivania M.; Apovian, Caroline M. (Frontiers in Endocrinology, 2019)
In patients with type 2 diabetes, bariatric surgery can lead to significant improvements in glycemic control and diabetes remission. We present a case of a Hispanic female with type 2 diabetes phenotype who underwent bariatric surgery and post-operatively stopped her insulin therapy due to multiple reasons, including decreased oral intake and concern for hypoglycemia. Ultimately, she developed diabetic ketoacidosis. She does not fit into the classical type 2 diabetes or type 1 diabetes definition but into the heterogeneous subgroup of diabetes called ketosis-prone diabetes.